Aged Callus Skeletal Stem/Progenitor Cells Contain an Inflammatory Osteogenic Population With Increased IRF and NF-κB Pathways and Reduced Osteogenic Potential - Lin, X.; Zhang, H.; Liu, J.; Wu, C L.; McDavid, A.; Boyce, B. F.; Xing, L. (Frontiers in Molecular Biosciences, 2022)
Skeletal stem/progenitor cells (SSPCs) are critical for fracture repair by providing osteo-chondro precursors in the callus, which is impaired in aging. However, the molecular signatures of callus SSPCs during aging is not known. Here, we performed single-cell RNA sequencing on 11,957 CD45-CD31-Ter119- SSPCs isolated from young and aged mouse calluses. Combining unsupervised clustering, putative makers, and DEGs/pathway analyses, major SSPC clusters were annotated as osteogenic, proliferating, and adipogenic populations. The proliferating cluster had a differentiating potential into osteogenic and adipogenic lineages by trajectory analysis. The osteoblostic/adipogenic/proliferating potential of individual clusters was further evidenced by elevated expression of genes related to osteoblasts, adipocytes or proliferation. The osteogenic cluster was sub-clustered into house-keeping and inflammatory osteogenic populations that were decreased and increased in aged callus, respectively. The majority of master regulators for the inflammatory osteogenic population belong to IRF and NF-B family, which was confirmed by immunostaining, RT-qPCR, and western blot analysis. Further, cells in the inflammatory osteogenic sub-cluster had reduced osteoblast differentiation capacity. In conclusion, we identified 3 major clusters in callus SSPCs, confirming their heterogeneity, and importantly, increased IRF/NF-B-mediated inflammatory osteogenic population with decreased osteogenic potential in aged cells.